LPG vehicles’ adoption in Portugal: lessons for new AFV diffusion - Jesus, Ana Paula Valente de (2022)
Nonetheless the efforts of the different players, namely oil companies and fuelling stations owners, the liquid petroleum gas (LPG) does not play the role of an alternative to traditional fossil fuels yet. So far, LPG vehicles (LPGV) have failed in being widely accepted by users. Currently, LPGVs’ sales are already being surpassed by the "pro-electrification" group of vehicles formed by hybrids (HEV) and battery-electric vehicles (BEV). So, while establishing a parallel with LPGVs and natural gas vehicles (NGV) diffusion and adoption lessons learned, this paper explores alternative fuel vehicles (AFV) purchase’s intentions determinants and the eventual influence of socio-demographic characteristics. The results of a survey carried out to 189 individuals show fundamental differences within gender as well as between education level groups. HEVs are on top of women purchase intention ranking while men express preferences towards BEVs. NGVs and fuel cell electric vehicles (FCEV) are newcomers in this ranking. Meanwhile, LPGVs confirm a declining trend. Among AFV’s purchase intention determinants, low emissions, clean energy sources, affordable energy, and environmental concerns are the most frequently stated. The results also reveal significant differences in perceived AFV’s features between educational level groups, highlighting post-graduates’ answers, which leads us to conclude that qualification plays an essential role in how potential buyers perceive the vehicles and influences the purchase decision-making process. Finally, in this study, we also give implications for improving users’ knowledge and perception of AFVs and suggestions for future research.